Perencanaan Strategis SWOT sebagai Kunci Keberlanjutan UMKM: Kajian Empiris Sektor Kuliner di Pontianak - Utami, Dwi; Oktavia, Deby (Sosiosaintika, 2025)
Amid post-pandemic turbulence, escalating technological disruption, and fluctuations in global commodity prices, the sustainability of culinary MSMEs in Pontianak City faces multidimensional challenges that demand comprehensive strategic transformation.This study aims to investigate in depth the anatomy of internal and external factors that determine the competitiveness of culinary MSMEs, as well as to formulate a sustainability strategy architecture based on the integration of Strengths, Weaknesses, Opportunities, and Threats (SWOT) analysis, the Resource-Based View (RBV) paradigm, and the principles of the circular economy. By adopting a descriptive qualitative method, data were collected through in-depth interviews, participatory observation, and documentation studies of culinary entities and local government regulations.The evaluation of the quantitative matrix indicates that culinary MSMEs in Pontianak possess competitive advantages in product authenticity and service flexibility, yet are constrained by a deficit in digital marketing literacy and inefficiencies in financial management. Opportunities for expansion through public space infrastructure and online food delivery aggregators are substantial, although accompanied by threats of market saturation from modern retail. The findings position MSMEs in Quadrant I (Aggressive), implying the urgency of implementing accelerated growth strategies.The managerial implications of this study recommend a transition toward holistic operational digitalization, capitalization on government legalization programs, and the adoption of zero-waste practices to reduce production costs and ensure long-term business resilience.